PATOGENESIS DAN DIAGNOSIS SINDROM KOLON IRITABEL - Jim, Edwin (Jurnal Biomedik : JBM, 2012)
Abstract: Irritable bowel syndrome (IBS) is a chronic functional bowel disorder characterized by abdominal pain or discomfort and alterations in bowel habits. Many factors play some important roles in the development of the IBS including abnormal motility, visceral hypersensitivity, and enteric infection. Diagnosis of IBS is based on Rome III criteria.Keywords: irritable bowel syndrome, pathogenesis, diagnosisAbstrak: Sindrom kolon iritabel (SKI) adalah penyakit gastrointestinal fungsional kronik yang ditandai oleh nyeri perut atau rasa tidak enak di perut dan gangguan kebiasaan defekasi. Banyak faktor yang menyebabkan terjadinya SKI antara lain gangguan motilitas, hipersensitivitas viseral, dan pasca infeksi usus. Saat ini kriteria diagnosis yang digunakan untuk SKI ialah kriteria Roma III.Kata kunci: sindrom kolon iritabel, patogenesis, diagnosis